2021
DOI: 10.1186/s12885-021-08777-6
|View full text |Cite
|
Sign up to set email alerts
|

ER expression associates with poor prognosis in male lung squamous carcinoma after radical resection

Abstract: Background Clinical options for lung squamous carcinoma (LUSC) are still quite limited. Carcinogenesis is an exceedingly complicated process involving multi-level dysregulations. Therefore, only looking into one layer of genomic dysregulation is far from sufficient. Methods We identified differentially expressed genes with consistent upstream genetic or epigenetic dysregulations in LUSC. Random walk was adopted to identify genes significantly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The remarkable controversy is probably due to many reasons, for instance, the patient population selected for research, the heterogeneous definitions of positivity, the differences in detecting methodology, and so on (14,15,34). Our previous finding indicated that the expression of ER predicted a poor clinical outcome in male LUSCs after receiving radical operation, which was also demonstrated by IHC assay (23). In present study, ER was significantly associated with DFS, OS, LRFS, and DMFS in male LUSCs after adjuvant sequential chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The remarkable controversy is probably due to many reasons, for instance, the patient population selected for research, the heterogeneous definitions of positivity, the differences in detecting methodology, and so on (14,15,34). Our previous finding indicated that the expression of ER predicted a poor clinical outcome in male LUSCs after receiving radical operation, which was also demonstrated by IHC assay (23). In present study, ER was significantly associated with DFS, OS, LRFS, and DMFS in male LUSCs after adjuvant sequential chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…The primary limitation of this study is the limited patient number (n=124), since we set a very strict enrollment criterion to reduce the potential bias. We only focused on male stage IIIA-N2 LUSCs with definitive molecular information of their EGFR and ALK status, and only patients strictly completed the sequential adjuvant chemoradiotherapy were enrolled, trying to validate the hypothesis inspired by our previous study (23). Additionally, this study is a single-center retrospective study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation